Estimates of cancer burden in Sicily. Issue 3 (May 2013) - Tumino, Rosario; Capocaccia, Riccardo; Traina, Adele; Madeddu, Anselmo; Contrino, Maria Lia; Zigon, Giulia
Aims and background: Estimates are complementary epidemiological measures which allow to present data on cancer burden, especially in geographical areas where measurements of cancer occurrence are not supported by exhaustive statistics on incidence, mortality and survival. The aim of this paper is to provide cancer incidence, mortality and prevalence estimates and projections for the major cancers in the period 1970—2015 for the entire region of Sicily. Methods: The estimates were computed by applying the MIAMOD method, a statistical back-calculation approach to derive incidence and prevalence figures starting from mortality and relative survival data. Published data from the Italian cancer registries were modeled in order to estimate the regional cancer survival. Results: In 2012 the most common cancers were breast cancer in women, colorectal cancer in both sexes, and prostate cancer in men, with about 4, 000, 3, 500 and 3, 000 estimated new cases, respectively. The highest crude mortality rates were estimated for lung cancer in men (63.6 per 100, 000) and breast cancer in women (30.8 per 100, 000) and the lowest for skin melanoma (both sexes) and cancer of the cervix uteri. For colorectal, lung and stomach cancer and skin melanoma, all the indicators were higher in men than women. The prevalence figures in women were more than 9 times the incidence figures for breast cancer and more than 10 times the incidence figures for skin melanoma. The prevalence was twice the incidence for lung cancer in both sexes. The prevalence increased for all the considered cancers except cervical cancer. Conclusion: According to our analyses in Sicily we expect about 14, 000 new diagnoses and 5, 500 deaths for the major cancer types in a year, while about 92, 000 persons with a diagnosis of the considered cancers were alive in 2012. We expect an increase in cancer survival and contemporary aging of the population: both expectations will inflate the cancer prevalence, causing more demand for oncology facilities.